Bioconversion of bread waste into high-quality proteins and biopolymers by fermentation of archaea Haloferax mediterranei - Unis, Razan; Gnaim, Rima; Kashyap, Mrinal; Shamis, Olga; Gnayem, Nabeel; Gozin, Michael; Liberzon, Alexander; Gnaim, Jallal; Golberg, Alexander (Frontiers in Microbiology, 2024)
The valorization of bread waste into high-quality protein and biopolymers using the halophilic microorganism Haloferax mediterranei presents a sustainable approach to food waste management and resource optimization. This study successfully coproduced protein and poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) biopolymer with a biomass content of 8.0 ± 0.1 g L⁻¹ and a productivity of 11.1 mg L⁻¹ h⁻¹. The fermentation process employed 3.0% w/v of enzymatically hydrolyzed bread waste. The amino acid profile of the cell biomass revealed a total content of 358 g kg⁻¹ of biomass dry weight (DW), including 147 g kg⁻¹ DW of essential amino acids. The protein quality, assessed through in-vitro enzyme digestion, indicated a high-quality protein with a digestibility value of 0.91 and a protein digestibility-corrected amino acid score (PDCAAS) of 0.78. The PHBV biopolymer component (36.0 ± 6.3% w/w) consisted of a copolymer of 3-hydroxybutyrate and 3-hydroxyvalerate in a 91:9 mol% ratio. This bioconversion process not only mitigates food waste but also generates valuable biomaterials.